Hemorragia pulmonar induzida por exercício: fatores predisponentes, prevenção e tratamento - Penachio, Daniel da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The Exercise Induced Pulmonar Haemorrhage (EIPH) affect a large amount of atlethe horses. It affects the horse's performance in any kind of competition and it can represent incresead spending of money or even an economic loss. Thoroughbred horses are the most affectef breed by EIPH because of intensive activity. Meanwhile any other kind of horse breed that is involved in athletic competition can also be affected by EIPH as well. In this brief work we are presenting the most common causes and factors from the EIPH as well the prevention and some types of treatment available nowadays

A Hemorragia Pulmonar Induzida por Exercício (HPIE) atinge grande parte dos cavalos atletas, interferindo no seu rendimento atlético e acarreta prejuízos econômicos significativos. O Puro Sangue Inglês de corrida é a raça mais afetada devido ao grande esforço a que é submetido, entretanto outras raças utilizadas para esporte podem ser afetadas pela HPIE. Neste trabalho são apresentadas as prováveis causas ou fatores predisponentes da HPIE assim como a prevenção e tratamentos utilizados na atualidade
Keywords: Pulmões - Hemorragia